Nodal status of central lymph nodes as a negative prognostic factor for papillary thyroid carcinoma1. Issue 7 (2nd May 2013) - Lee, Yoon Se; Lim, Yun‐Sung; Lee, Jin‐Choon; Wang, Soo‐Geun; Kim, In‐Ju; Son, Seok‐Man; Shin, Dong Hoon; Lee, Byung‐Joo
Abstract Background The status of metastatic lymph nodes, including the size and extracapsular spread (ECS), in papillary thyroid cancer (PTC) has not been well established. This study evaluated the correlation between the specific status of central lymph node metastases (CLNM) and negative prognostic factors. Methods We reviewed 243 patients who underwent total thyroidectomy and neck dissection. The CLNM slides were reviewed and the relationship between the CLNM status and risk factors was analyzed. Results CLNM were found in 111 patients. ECS (+) was related to a large tumor, high number of CLNM, and large node (P < 0.05). Tumor size and number of CLNM were related to the ECS rate (OR = 3.861 and 2.491, respectively; P < 0.01) in a multivariate analysis. Large nodes (≥6 mm) were related to large tumor size, extrathyroidal extension, number of CLNM, and lateral cervical lymph node metastasis (LNM). Tumor size and LNM (OR = 4.519 and 7.811, respectively; P < 0.05) were related to large nodes in a multivariate analysis. Conclusions ECS was related to node size, tumor size, and number of CLNM. Node size was related to tumor size and LNM. Thus, specific nodal status is a possible prognostic factor for PTC. J. Surg. Oncol. 2013;107:777–782. © 2012 Wiley Periodicals, Inc.